Perception of persons with severe or profound deafness about the communication process during health care Percepción de la persona con sordera severa y/o profunda acerca del proceso de comunicación durante su atención de salud Percepção da pessoa com surdez severa e/ou profunda acerca do processo de comunicação durante seu atendimento de saúde - Adriane Helena Alves Cardoso; Karla Gomes Rodrigues; Maria Márcia Bachion (Universidade de São Paulo, 2006)
This study describes a qualitative approach with the objective of characterizing the perceptions of people with severe or profound deafness about the communication process in the context of health care services. Study participants were 11 people with severe and/or profound deafness, who were interviewed using Brazilian sign language (LIBRAS). The interactions were videotaped and then transcribed. Care was taken to maintain the grammatical construction which was characteristic in the expression of each person. Three categories emerged from thematic analysis: Understanding, Need for Mediation, Feelings. Deaf persons do not achieve effective communication in health care, during which they experience negative feelings. Hence, the presence of a professional interpreter is needed. La finalidad de este estudio descriptivo con aproximación cualitativa fue caracterizar las percepciones de personas con sordera severa o profunda sobre el proceso de la comunicación en el contexto de su atención por profesionales de salud. Participaron once personas con sordera severa y/o profunda, que fueron entrevistadas mediante el lenguaje brasileño de signos (LIBRAS). Las interacciones fueron grabadas en cintas VHS y transcritas, manteniéndose la construcción gramatical característica de su expresión. Mediante análisis temático emergieron tres categorías: Entendimiento, Necesidad de Intermediación y sentimientos. El sordo no alcanza una comunicación eficaz durante la atención de salud, en la cual experimenta sentimientos negativos, necesitando la presencia de un profesional intérprete. Este estudo descritivo de abordagem qualitativa teve o objetivo de caracterizar as percepções da pessoa com surdez severa ou profunda sobre o processo de comunicação no contexto do seu atendimento por profissionais de saúde. Participaram 11 pessoas com surdez severa e/ou profunda, as quais foram entrevistadas usando-se LIBRAS. As interações foram gravadas em fitas VHS e transcritas, mantendo-se a construção gramatical característica da expressão destas pessoas. Mediante análise temática emergiram três categorias: Entendimento, Necessidade de Intermediação e Sentimentos. O surdo não tem alcançado uma comunicação efetiva durante o atendimento de saúde, no qual experimenta sentimentos negativos, necessitando da presença de um profissional intérprete.